Intracellular Zn2+ signaling in the dentate gyrus is required for object recognition memory. Issue 11 (4th July 2014) - Takeda, Atsushi; Tamano, Haruna; Ogawa, Taisuke; Takada, Shunsuke; Nakamura, Masatoshi; Fujii, Hiroaki; Ando, Masaki
ABSTRACT The role of perforant pathway‐dentate granule cell synapses in cognitive behavior was examined focusing on synaptic Zn2+ signaling in the dentate gyrus. Object recognition memory was transiently impaired when extracellular Zn2+ levels were decreased by injection of clioquinol and N, N, N′, N′‐tetrakis‐(2‐pyridylmethyl) ethylendediamine. To pursue the effect of the loss and/or blockade of Zn2+ signaling in dentate granule cells, ZnAF‐2DA (100 pmol, 0.1 mM/1 µl), an intracellular Zn2+ chelator, was locally injected into the dentate molecular layer of rats. ZnAF‐2DA injection, which was estimated to chelate intracellular Zn2+ signaling only in the dentate gyrus, affected object recognition memory 1 h after training without affecting intracellular Ca2+ signaling in the dentate molecular layer. In vivo dentate gyrus long‐term potentiation (LTP) was affected under the local perfusion of the recording region (the dentate granule cell layer) with 0.1 mM ZnAF‐2DA, but not with 1–10 mM CaEDTA, an extracellular Zn2+ chelator, suggesting that the blockade of intracellular Zn2+ signaling in dentate granule cells affects dentate gyrus LTP. The present study demonstrates that intracellular Zn2+ signaling in the dentate gyrus is required for object recognition memory, probably via dentate gyrus LTP expression. © 2014 Wiley Periodicals, Inc.